Integrating Minahasa Folklore Values Through Digital Media in Indonesian Language Learning: A Case Study at SMK Negeri 1 Tombariri - Margareth Winokan; Santje Iroth; Grace S.Luntungan (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study investigates the integration of Minahasa cultural values through digital media in Indonesian language learning at SMK Negeri 1 Tombariri. Employing a qualitative descriptive approach, the research focuses on the use of Canva digital posters in teaching the folklore